The resveratrol trimer miyabenol C inhibits β-secretase activity and β-amyloid generation. - Jin Hu; Ting Lin; Yuehong Gao; Junyue Xu; Chao Jiang; Guanghui Wang; Guojun Bu; Huaxi Xu; Haifeng Chen; Yun-wu Zhang (PLoS ONE)
Accumulation and deposition of amyloid-β peptide (Aβ) in the brain is a primary cause of the pathogenesis of Alzheimer's disease (AD). Aβ is generated from amyloid-β precursor protein (APP) through sequential cleavages first by β-secretase and then by γ-secretase. Inhibiting β-secretase activity is believed to be one of the most promising strategies for AD treatment. In the present study, we found that a resveratrol trimer, miyabenol C, isolated from stems and leaves of the small-leaf grape (Vitisthunbergii var. taiwaniana), can markedly reduce Aβ and sAPPβ levels in both cell cultures and the brain of AD model mice. Mechanistic studies revealed that miyabenol C affects neither protein levels of APP, the two major α-secretases ADAM10 and TACE, and the γ-secretase component Presenilin 1, nor γ-secretase-mediated Notch processing and TACE activity. In contrast, although miyabenol C has no effect on altering protein levels of the β-secretase BACE1, it can inhibit both in vitro and in vivo β-secretase activity. Together, our results indicate that miyabenol C is a prominent β-secretase inhibitor and lead compound for AD drug development.